0+0.99d=10+0.89d

Simple and best practice solution for 0+0.99d=10+0.89d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0+0.99d=10+0.89d equation:


Simplifying
0 + 0.99d = 10 + 0.89d
Remove the zero:
0.99d = 10 + 0.89d

Solving
0.99d = 10 + 0.89d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-0.89d' to each side of the equation.
0.99d + -0.89d = 10 + 0.89d + -0.89d

Combine like terms: 0.99d + -0.89d = 0.1d
0.1d = 10 + 0.89d + -0.89d

Combine like terms: 0.89d + -0.89d = 0.00
0.1d = 10 + 0.00
0.1d = 10

Divide each side by '0.1'.
d = 100

Simplifying
d = 100

See similar equations:

| (72x-65y)-(62x+15Y)= | | -x=2-6 | | 0.99+0=10+0.89 | | (62x+63y)-(11x-8y)= | | x+(8)=-12 | | (60x+52y)-(11x-3y)= | | (49x+69y)-(-31x+8y)= | | 12x^2-180x+500=0 | | 8(5bx+y)=39bx-6y | | (4w-9)(1-w)=0 | | y-10=-7 | | 5x+30-2=9x | | 2n+21=5n+3 | | X^2+3x-4=6 | | x+375=925 | | f(x)=x+7 | | 24+8m=0 | | 144=2(6+2x)+2(x) | | y=-3.6x+6.4 | | 24+8m=424 | | 180+0.55*x=327.95 | | 2x^2+14x+35=0 | | 160+1.05*x=443.50 | | 27x+3y=-6 | | 2(6+x)-4x=2 | | 1x+0.14x=285 | | 9(10n^2-2)-5(18n^2+7)= | | (6-z)(4z+9)=0 | | (-7x^5-3x^2+6x)-(1x^5-10x^2-5)= | | -x-3=-x+2 | | 41.73+0.20m=130 | | 0.375x-0.2x+10=0.3 |

Equations solver categories